Navigating Organizational Power Struggles Through Authentic Leadership in Higher Education: A Narrative Grounded Theory of Conscience and Spiritual Intelligence - Novebri Novebri; Sri Rahayu Retnowulan; Aan Komariah; Dedy Achmad Kurniady; Asep Suryana; Bashori B (Paedagogia: Jurnal Pendidikan, 2026)
Authentic leadership today faces significant challenges stemming from shifts in power that can lead to tensions between moral values, conscience, and organizational interests. This study explores how authentic leadership can be realized and maintained within the context of power within higher education, emphasizing the role of conscience and spiritual intelligence. Using a narrative approach and grounded theory, the stories and experiences of leaders in higher education are analyzed in depth. The themes of authenticity in decision-making, interpersonal relationships, and leaders' experiences interacting with organizational processes are explored in detail. Data collection was conducted through in-depth interviews, observation, and documentation. Data were analyzed through an iterative coding process accompanied by continuous comparisons between categories until category refinement was achieved. Then, various sources were combined to find the main concepts and relationships based on stories from research informants. The results of the analysis indicate that authentic leadership does not only depend on self-awareness, transparency, consistency, and harmony between personal values ​​and real actions, but is closely related to the complex interaction between the voice of conscience as an internal moral guide that supports integrity when facing pressure with spiritual intelligence as a basis for understanding and responding to ethical problems wisely. This study theoretically helps broaden the understanding of authentic leadership. This research focuses on moral and spiritual perspectives. These two elements serve as mutually supportive foundations for leaders to remain authentic despite facing pressure from organizational power. The findings indicate that the implementation of real leadership in higher education is not merely a leadership style but a continuous process of maintaining the moral commitment and social responsibility of academic institutions amidst the dynamics of organizational power.